Battery technology for electric vehicles : public science and private innovation - Link, Albert N.; O'Connor, Alan C; Scott, Troy J. (Routledge, Earthscan, 2015)
Electric drive vehicles (EDVs) are seen on American roads in increasing numbers. Related to this market trend and critical for it to increase are improvements in battery technology. Battery Technology for Electric Vehicles examines in detail at the research support from the U.S. Department of Energy (DOE) for the development of nickel-metal-hydride (NiMH) and lithium-ion (Li-ion) batteries used in EDVs. With public support comes accountability of the social outcomes associated with public investments. The book overviews DOE investments in advanced battery technology, documents the adoption of.